Mathematical Modelling to Guide Drug Development for Malaria Elimination. Issue 3 (March 2017) - Slater, Hannah C.; Okell, Lucy C.; Ghani, Azra C.
Abstract : Mathematical models of the dynamics of a drug within the host are now frequently used to guide drug development. These generally focus on assessing the efficacy and duration of response to guide patient therapy. Increasingly, antimalarial drugs are used at the population level, to clear infections, provide chemoprevention, and to reduce onward transmission of infection. However, there is less clarity on the extent to which different drug properties are important for these different uses. In addition, the emergence of drug resistance poses new threats to longer-term use and highlights the need for rational drug development. Here, we argue that integrating within-host pharmacokinetic and pharmacodynamic (PK/PD) models with mathematical models for the population-level transmission of malaria is key to guiding optimal drug design to aid malaria elimination. Trends: Antimalarial drugs are being used in many different contexts beyond treatment of disease – increasingly with the aim of reducing malaria transmission in a community. Each drug has different attributes – killing efficacy against asexual parasites, duration of effect, gametocytocidal activity, mosquitocidal activity, liver-stage activity (for Plasmodium vivax ), dosing schedule and toxicity. Drug attributes need to be rationally combined to match their usage aims based on a quantitative understanding of their properties. For transmission reductions, the individual patient approach is less relevant and a population-level perspective is critical. Rational approaches to combining drugs with other forms of malaria control to reduce malaria transmission can only be made using transmission models informed by field data, given the difficulty of testing all combinations of interventions in all settings.